2017
DOI: 10.1093/rpd/ncx254
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Response of Passive Dosimetry Systems in Scanning Proton Radiotherapy—a Study Using Paediatric Anthropomorphic Phantoms

Abstract: Proton beam therapy has advantages in comparison to conventional photon radiotherapy due to the physical properties of proton beams (e.g. sharp distal fall off, adjustable range and modulation). In proton therapy, there is the possibility of sparing healthy tissue close to the target volume. This is especially important when tumours are located next to critical organs and while treating cancer in paediatric patients. On the other hand, the interactions of protons with matter result in the production of seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 12 publications
2
39
1
Order By: Relevance
“…The data for the bubble detectors placed inside a water tank irradiated with an energy range between 62.7 and 89.8 meV used for eye treatments (Ciocca et al 2019) suggest that H is about ten times lower than those obtained in the present study for a similar primary proton energy used for the lung treatment. Unexpectedly, for a brain tumor of 65 cm 3 volume located inside a paediatric phantom irradiated with proton PBS of energies in the range 70-140 meV (Knežević et al 2018), the H measured with track-etched detectors showed similar values as the ones simulated in the present study for the lung tumour with a target volume twice as large and much lower primary proton energy. In addition, the H measured with track-etched detectors by Stolarczyk et al (2018), for a 1000 cm 3 target volume located inside a water tank irradiated with proton PBS at an energy range of 120-170 meV, is comparable to the H measured with the same detector type in an adult human phantom treated for prostate cancer (Hälg et al 2014), and to the H simulated in the present study for the prostate tumour, despite a five times bigger target volume and slightly lower primary proton energy.…”
Section: Neutron Dose Equivalentsupporting
confidence: 81%
See 2 more Smart Citations
“…The data for the bubble detectors placed inside a water tank irradiated with an energy range between 62.7 and 89.8 meV used for eye treatments (Ciocca et al 2019) suggest that H is about ten times lower than those obtained in the present study for a similar primary proton energy used for the lung treatment. Unexpectedly, for a brain tumor of 65 cm 3 volume located inside a paediatric phantom irradiated with proton PBS of energies in the range 70-140 meV (Knežević et al 2018), the H measured with track-etched detectors showed similar values as the ones simulated in the present study for the lung tumour with a target volume twice as large and much lower primary proton energy. In addition, the H measured with track-etched detectors by Stolarczyk et al (2018), for a 1000 cm 3 target volume located inside a water tank irradiated with proton PBS at an energy range of 120-170 meV, is comparable to the H measured with the same detector type in an adult human phantom treated for prostate cancer (Hälg et al 2014), and to the H simulated in the present study for the prostate tumour, despite a five times bigger target volume and slightly lower primary proton energy.…”
Section: Neutron Dose Equivalentsupporting
confidence: 81%
“…The available literature on dose measurements in proton radiotherapy using a human phantom shows that the most studied cases involve tumours located in the head and that doses to other organs were not given (La Tessa et al 2012), or where data on the mean organ distance to the target volume were not given (Stolarczyk et al 2011). Furthermore, a comparison of the results obtained in the present study could not be done with those obtained by (Knežević et al 2018) because the phantom used by these authors was of another size.…”
Section: Figmentioning
confidence: 78%
See 1 more Smart Citation
“…RPLs were calibrated in terms of kerma free-in-air, K air , using a 60 Co source and then converted to D w using experimentally determined factors (Knežević et al 2013). For determining the uncertainty of dose calculation for TLDs and RPLs, the same procedures were used as presented in Knežević et al (2013Knežević et al ( , 2018 and Stolarczyk et al (2018). Particular calculated uncertainties are presented in the table 2 in the supplementary data.…”
Section: Luminescence Detectors Used For Out-of-field Photon and Neutmentioning
confidence: 99%
“…Pairs of 6 LiF/ 7 LiF thermoluminescence detectors are used in dosimetry to discriminate between neutron and gamma-ray doses. The difference in response between 6 LiF and 7 LiF detectors, caused by the higher 6 Li cross section in the Li(n,α)T reaction, is expressed in terms of the gamma-equivalent neutron dose, D n (Knežević et al 2018). However, this quantity cannot be used to infer neutron dose equivalent because the dose in tissue is predominately produced by high energy neutrons whereas 6 Li reacts mainly with thermal neutrons.…”
Section: The Correlation Between Gamma-equivalent Neutron Dose and Domentioning
confidence: 99%